2019
DOI: 10.1128/aac.02152-18
|View full text |Cite
|
Sign up to set email alerts
|

Iron Chelator Deferasirox Reduces Candida albicans Invasion of Oral Epithelial Cells and Infection Levels in Murine Oropharyngeal Candidiasis

Abstract: Candida albicans, the causative agent of mucosal infections, including oropharyngeal candidiasis (OPC), as well as bloodstream infections, is becoming increasingly resistant to existing treatment options. In the absence of novel drug candidates, drug repurposing aimed at using existing drugs to treat off-label diseases is a promising strategy. C. albicans requires environmental iron for survival and virulence, while host nutritional immunity deploys iron-binding proteins to sequester iron and reduce fungal gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…We therefore wished to test whether these represented potential targets to combat C. albicans growth in high CO 2 environments such as the airway. An Fe 3+ chelator called Deferasirox, which is approved for treating patients with iron overload, has recently been shown to reduce infection levels in a murine oropharyngeal candidiasis model 63 . With this in mind, we repeated our previous iron starvation biofilm growth assay (Figure 4B) using Deferasirox in place of Ferrozine.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore wished to test whether these represented potential targets to combat C. albicans growth in high CO 2 environments such as the airway. An Fe 3+ chelator called Deferasirox, which is approved for treating patients with iron overload, has recently been shown to reduce infection levels in a murine oropharyngeal candidiasis model 63 . With this in mind, we repeated our previous iron starvation biofilm growth assay (Figure 4B) using Deferasirox in place of Ferrozine.…”
Section: Resultsmentioning
confidence: 99%
“…As discussed by Puri et al (2019), iron-related regulation in C. albicans is mainly mediated by four regulators, Tup1, Hap43, Sfu1 and Sef1 22 . Our mutant library screening data demonstrated that PMT12-BF4-associated iron-related genes were regulated by these regulators, and most of these genes were repressed by Hap43, indicating the antifungal activity of PMT12-BF4 may not directly alter the iron concentration in the environment, but instead, it possibly interferes with functions of iron regulation.…”
Section: Discussionmentioning
confidence: 98%
“…Drug repurposing has been proposed as an alternative for new therapeutic applications using FDA-approved drugs 1 . Repurposed drugs have been explored as antimicrobial treatments to target pathogens [33][34][35][36][37] . Previously, either free or nanoparticle carrier (NPC) loaded TB was tested for repurposing as antimycotic and antibacterial agents, with promising in vitro data 19,30 .…”
Section: Discussionmentioning
confidence: 99%